The Impact of Policy on Somali Refugee Women in Canada - Spitzer, Denise L. (Refuge: Canada's Journal on Refugees, 2006)
This paper explores the ways in which government policy and public discourse have operated to enhance and maintain the liminal status of Somali women refugees in Canada, and the ways in which Somali Canadian women have resisted these efforts in order to create meaning and a place for themselves and their families in North America. The policies and practices that obliged many Somali women to wait three to five years to apply for permanent residency status, Eurocentric definitions of the family that constrain family unification strategies, and economic marginalization due to lack of recognition of foreign credentials have had cumulative adverse effects on the health and well-being of Somali women in Canada.